Anaokulu Öğretmenlerinin Beş ve Altı Yaş Çocukları İçin Kullandıkları Masal ve Hikâye Kitaplarının Niteliklerinin İncelenmesi - Mübeccel Gönen (Türk Kütüphaneciliği)
This study aims to investigate the quality of tales and story books used by nursery teachers for children aged 5-6. For this purpose, 17 teachers in six kindergartens were inten’iewed, and 321 books which were available in these kindergartens were evaluated. The evaluation considered contents, illustrations and physical quality. The results are that the books are not satisfactory in these respects and teachers do not have sufficient background in "Children's Literature ".